A Noninvasive Multianalytical Approach for Lung Cancer Diagnosis of Patients with Pulmonary Nodules. Issue 13 (7th May 2021) - Liu, Quan‐Xing; Zhou, Dong; Han, Tian‐Cheng; Lu, Xiao; Hou, Bing; Li, Man‐Yuan; Yang, Gui‐Xue; Li, Qing‐Yuan; Pei, Zhi‐Hua; Hong, Yuan‐Yuan; Zhang, Ya‐Xi; Chen, Wei‐Zhi; et al.
Abstract: Addressing the high false‐positive rate of conventional low‐dose computed tomography (LDCT) for lung cancer diagnosis, the efficacy of incorporating blood‐based noninvasive testing for assisting practicing clinician's decision making in diagnosis of pulmonary nodules (PNs) is investigated. In this prospective observative study, next generation sequencing‐ (NGS‐) based cell‐free DNA (cfDNA) mutation profiling, NGS‐based cfDNA methylation profiling, and blood‐based protein cancer biomarker testing are performed for patients with PNs, who are diagnosed as high‐risk patients through LDCT and subsequently undergo surgical resections, with tissue sections pathologically examined and classified. Using pathological classification as the gold standard, statistical and machine learning methods are used to select molecular markers associated with tissue's malignant classification based on a 98‐patient discovery cohort (28 benign and 70 malignant), and to construct an integrative multianalytical model for tissue malignancy prediction. Predictive models based on individual testing platforms have shown varying levels of performance, while their final integrative model produces an area under the receiver operating characteristic curve (AUC) of 0.85. The model's performance is further confirmed on a 29‐patient independent validation cohort (14 benign and 15 malignant, with power > 0.90), reproducing AUC of 0.86, which translates to an overall sensitivity of 80% and specificity of 85.7%. Abstract : An integrative multianalytical machine learning model based on patient clinical features, cfDNA mutation, cfDNA methylation, and protein cancer biomarkers for noninvasive cancer diagnosis of lung pulmonary nodules has achieved an area under the receiver operating characteristic curve of 0.85 on a 98‐patient discovery cohort, and 0.86 on a 29‐patient independent validation cohort, translating to 80% sensitivity and 85.7% specificity.